2008
DOI: 10.1093/europace/eun211
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive administration of atropine and isoproterenol for the evaluation of asymptomatic sinus bradycardia

Abstract: In patients with deficient chronotropic response to atropine administration, isoproterenol tests could differentiate those with inadequate chronotropic reserves, possibly requiring preventive pacemaker implantations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These include atrial electroanatomic remodeling, previous cardiac surgery, decreased left ventricular ejection fraction, and increased temporal recovery of the sinus node function (Daoud et al, 2002;Koplan et al, 2003;Sairaku et al, 2012). Direct damage to the sinus node or sinus node blood supply during cardiac surgery has been suggested as the causal mechanism (Nerantzis et al, 2021), als with asymptomatic sinus bradycardia when there is an abnormal response to both atropine (<90 bpm) and isoproterenol (<120 bpm) (Vavetsi et al, 2008). The present case also showed a poor response to atropine and isoproterenol.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These include atrial electroanatomic remodeling, previous cardiac surgery, decreased left ventricular ejection fraction, and increased temporal recovery of the sinus node function (Daoud et al, 2002;Koplan et al, 2003;Sairaku et al, 2012). Direct damage to the sinus node or sinus node blood supply during cardiac surgery has been suggested as the causal mechanism (Nerantzis et al, 2021), als with asymptomatic sinus bradycardia when there is an abnormal response to both atropine (<90 bpm) and isoproterenol (<120 bpm) (Vavetsi et al, 2008). The present case also showed a poor response to atropine and isoproterenol.…”
Section: Discussionmentioning
confidence: 56%
“…Atropine can return an acute SND condition to a normal sinus rhythm (Wallace et al, 2021), and Spiridoula. el found that combined atropine–isoproterenol tests can evaluate the indication for preventive permanent pacemaker implantation in individuals with asymptomatic sinus bradycardia when there is an abnormal response to both atropine (<90 bpm) and isoproterenol (<120 bpm) (Vavetsi et al, 2008). The present case also showed a poor response to atropine and isoproterenol.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, HR max might represent the HR reserve, and compromised HR max value should be related to injured HR reserve, resulting in tendency to RVP dependence. It was reported that HR reserve could partly represent the function of cardiac conduction system, especially the sinus node function, 23,24 and this offered indirect evidence to support this perspective. Nevertheless, ROC analysis disclosed that HR max failed to accurately predict RVP dependence ( Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of irreversible lesions of the sinus node should be considered if there is no or slight response to atropine; however, these outcomes cannot completely rule out the vagal inhibitory effect. The following conditions may contribute to a mismatch between the AT outcomes and the actual situation: 1) using a conventional dose of atropine in overweight or obese subjects is not sufficient to provoke noticeable response owing to the limitation in maximum dosage; low-dose atropine may in cause paradoxical bradycardia ( Mandel et al, 1972 ); 2) subjects are insensitive to atropine; 3) Differences in the amount and quality of the cholinergic receptors among individuals ( Vavetsi et al, 2008 ); 4) taking drugs that would suppress sinus node pacemaking; 5) high sympathetic tone partially masks the intrinsic sinus node involvement.…”
Section: Selection Criteria For Patients Undergoing Cardioneuroablati...mentioning
confidence: 99%